ASH2L upregulation contributes to diabetic endothelial dysfunction in mice through STEAP4-mediated copper uptake - Zhong Wen; Dong Ye-jun; Hong Chen; Li Yu-hui; Xiao Chen-xi; Liu Xin-hua; Chang Jun (Acta Pharmacologica Sinica; Vol 45, No 3 (March 2024): Acta Pharmacologica Sinica, 2024)
Endothelial dysfunction is a common complication of diabetes mellitus (DM) and contributes to the high incidence and mortality of cardiovascular and cerebrovascular diseases. Aberrant epigenetic regulation under diabetic conditions, including histone modifications, DNA methylation, and non-coding RNAs (ncRNAs) play key roles in the initiation and progression of diabetic vascular complications. ASH2L, a H3K4me3 regulator, triggers genetic transcription, which is critical for physiological and pathogenic processes. In this study we investigated the role of ASH2L in mediating diabetic endothelial dysfunction. We showed that ASH2L expression was significantly elevated in vascular tissues from diabetic db/db mice and in rat aortic endothelial cells (RAECs) treated with high glucose medium (11 and 22 mM). Knockdown of ASH2L in RAECs markedly inhibited the deteriorating effects of high glucose, characterized by reduced oxidative stress and inflammatory responses. Deletion of endothelial ASH2L in db/db mice by injection of an adeno-associated virus (AAV)-endothelial specific system carrying shRNA against Ash2l (AAV-shAsh2l) restored the impaired endothelium-dependent relaxations, and ameliorated DM-induced vascular dysfunction. We revealed that ASH2L expression activated reductase STEAP4 transcription in vitro and in vivo, which consequently elevated Cu(I) transportation into ECs by the copper transporter CTR1. Excess copper produced by STEAP4-mediated copper uptake triggered oxidative stress and inflammatory responses, resulting in endothelial dysfunction. Our results demonstrate that hyperglycemia triggered ASH2L-STEAP4 axis contributes to diabetic endothelial dysfunction by modulating copper uptake into ECs and highlight the therapeutic potential of blocking the endothelial ASH2L in the pathogenesis of diabetic vascular complications.